Influence of vacuum packaging on certain chemical qualities of mutton" - DUSHYANTHAN, K; SHANMUGAM, A M; VENKATARAMANUJAM, V (The Indian Journal of Animal Sciences, 2014)
The influence of vacuum packing on extract release volume (ERv); thiobarbituric acid (TBA) number and tyrosine value (TV) of mutton packed under 2 methods, in 4 packaging materials and stored for different periods under chiller (5Â±2Â°C) and freezer (-10’C) temperatures, was studied. Mutton packed under vacuum and stored at both chiller and freezer temperatures revealed higher ERV and lower TBA number and TV. Multilayer (ML) material was the most suitable material for packaging mutton under vacuum and storing at both chiller and freezer temperatures. Mutton packed in ML material had the highest ERV and the lowest TBA number and TV. The anaerobic environment created by the vacuum method and the barrier properties of ML material for oxygen led to the lower proteolysis. As the storage period increased at both chiller and freezer temperature there was an increase in TBA number and TV of mutton, whereas ERV of mutton decreased with increase in storage at chiller temperatures and increased with increase in storage at freezer temperatures. The influence of vacuum packaging has brought about a better effect by improving the ERV, TBA number and TV of mutton.